Shuri - Stone, Nic (Scholastic Inc., 2020)
Shuri, thirteen-year-old princess from Wakonda and sister to the Black Panther, discovers that the heart-shape herb, which gives the Black Panther his powers, is dying. While tribal leaders quarrel, Shuri sets out with guardian-in-training, K'Marah, to discover what is causing the plant to die and how to reverse the damage.